Mask wearing as a prosocial behavior: Proposing and testing the moral norms activation model - Monique M. Turner; Youjin Jang; Ruth Heo; Qijia Ye; Rachel Wade; Maria Knight Lapinski; Tai-Quan Peng (PLoS ONE, 2025)
The aim of this study was to develop and test a model of prosocial prevention behavior during COVID-19, termed the Moral Norms Activation Model (MNAM). This model examines how moral norms, influenced by awareness of consequences, predict prosocial prevention behaviors, such as mask-wearing, and the role of perceived severity and collective orientation as moderating factors. We conducted a survey during the early months of the COVID-19 pandemic with a nationally representative sample of U.S. adults (N = 8,778). The survey measured awareness of consequences, moral norms, anticipated guilt, perceived severity, collective orientation, and self-reported mask-wearing behavior. A series of regressions was used to test the proposed model and interactions. Findings supported the MNAM, demonstrating that awareness of consequences was a significant direct predictor of moral norms. These moral norms, in turn, predicted prosocial prevention behavior, mediated by anticipated guilt. The moderating effects of perceived severity and collective orientation were also significant, reinforcing the strength of the association between moral norms and behavior in individuals with high collective orientation and greater perceived severity. The results highlight the critical role of moral norms and anticipated guilt in promoting prosocial health behaviors during a collective health crisis. The MNAM provides a novel framework for understanding how individual psychological processes contribute to public health behaviors. These findings suggest that public health campaigns emphasizing moral responsibility and awareness of consequences could enhance compliance with preventive measures.